IMPLEMENTASI KEBIJAKAN REVITALISASI PASAR TRADISIONAL NAMBANGAN DI KOTA SURABAYA - Shafira Rohmadani; Suci Megawati (Universitas Negeri Surabaya, 2022)
Traditional markets are one of the important sectors in a country's economy, but at this time traditional market conditions are threatened due to the growing modern market, as well as e-comerce. In addition, the existence of poor traditional market visualization in the community becomes a threat. The problem studied is the implementation of traditional market revitalization policies in Surabaya. The purpose of this research is to find out how the implementation of traditional market revitalization policies in Surabaya by using the theory of implementation stages according to (Tachjan, 2006). This study uses descriptive research with qualitative approaches, data gathering methods namely interviews, and documentation. The data sources used are primary and secondary sources. Data analysis used interactive models according to Miles and Huberman (1992). The main actors of physical revitalization and management policies are civil servant coordinators and market escorts through the Cooperative and Micro Enterprises Office who participate in involving other agencies in the implementation of policies. The policy actors involved carry out their tupoksi using predetermined methods and procedures. Supervision on the policy is carried out every day and on the physical revitalization of the agencies involved has carried out the tupoksi well, and on the revitalization of management there needs to be strict supervision. The conclusion of this study is that physical revitalization has been carried out well as shown by all the agencies involved are able to carry out their tupoksi well. While the revitalization of management still needs to be improved for more optimal results. Researchers put forward further suggestions that can be done related to the revitalization of market management, namely market managers who conduct a more stringent monitoring and monitoring system. Keywords: Implementation, Policy, Revitalization, Traditional Markets